2013
DOI: 10.1007/s13595-013-0327-3
|View full text |Cite
|
Sign up to set email alerts
|

Fuel vertical structure affects fire sustainability and behaviour of prescribed burning in Spartium junceum shrublands

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Most fuel observations in the dataset (65%) followed the field protocol described by and Bovio et al (2014). This uses a mixed approach with both destructive (i.e., vegetation removed and analyzed in the laboratory) and non-destructive techniques (see next paragraph), such as indirect estimates of fuel loads based on allometry equations (Corona et al 2012, Castagneri et al 2013, Sirca et al 2016, Conti et al 2019. The remaining 35% of survey data adopted protocols that are similar to the ones mentioned, but applied a fully destructive sampling to the shrub component, as they were mostly carried out in shrubland fuelbeds (Bacciu et al 2009, Duce et al 2012, Castagneri et al 2013, Vacchiano et al 2014.…”
Section: Sampling Designmentioning
confidence: 99%
“…Most fuel observations in the dataset (65%) followed the field protocol described by and Bovio et al (2014). This uses a mixed approach with both destructive (i.e., vegetation removed and analyzed in the laboratory) and non-destructive techniques (see next paragraph), such as indirect estimates of fuel loads based on allometry equations (Corona et al 2012, Castagneri et al 2013, Sirca et al 2016, Conti et al 2019. The remaining 35% of survey data adopted protocols that are similar to the ones mentioned, but applied a fully destructive sampling to the shrub component, as they were mostly carried out in shrubland fuelbeds (Bacciu et al 2009, Duce et al 2012, Castagneri et al 2013, Vacchiano et al 2014.…”
Section: Sampling Designmentioning
confidence: 99%
“…Fuel moisture content is an important predictor of fuel flammability (Castro et al, 2003;Pellizzaro et al, 2007), and has been increasingly applied in fire risk assessment (Chuvieco et al, 2004a;Tanase et al, 2015). Since fine fuel, including leaves and thin shoots, is highly combustible, fuel type plays a critical role in wildfire initiation and propagation (Castagneri et al, 2013;Clark et al, 2014). Therefore, to better understand how differences in fuel flammability may affect fire risk in forests with different species composition and structure, we should compare the moisture content of fine fuels among different communities (Johnston et al, 2015).…”
Section: Biotic and Abiotic Controls On Pmcmentioning
confidence: 99%
“…In addition to moisture content, oil and aromatic compounds, such as terpenes, in plant tissue are also critical features influencing fuel flammability (Ormeño et al, 2008). Moreover, other studies have found the vertical structure of fuel materials is critical for the potential of fire propagation (Castagneri et al, 2013), and that forest litter has distinct spatial distribution and flammability from living fuel (Varner et al, 2015). Therefore, further studies need to integrate the physical and chemical features of fuel in order to better understand the inherent complexity of the flammability of different forest types and to more accurately predict the behavior of fire in this region.…”
Section: Biotic and Abiotic Controls On Pmcmentioning
confidence: 99%
“…Likewise, canopy height and canopy bulk density can affect fire intensity and burn severity in different tree species [10][11][12][13]. Information on how fuel density varies from the surface layer, the ladder layer, to the canopy layer is critical for understanding fire intensities and has implications for subsequent fuel management [14,15].…”
Section: Introductionmentioning
confidence: 99%